Model-based dissection of CD95 signaling dynamics reveals both a pro- and antiapoptotic role of c-FLIPL - Fricker, Nicolai Benjamin; Beaudouin, Joël; Richter, Petra; Eils, Roland; Krammer, Peter H.; Lavrik, Inna N. (The journal of cell biology, 2010)
Cellular FADD-like interleukin-1β-converting enzyme inhibitory proteins (c-FLIPs; isoforms c-FLIP long [c-FLIPL], c-FLIP short [c-FLIPS], and c-FLIP Raji [c-FLIPR]) regulate caspase-8 activation and death receptor (DR)-induced apoptosis. In this study, using a combination of mathematical modeling, imaging, and quantitative Western blots, we present a new mathematical model describing caspase-8 activation in quantitative terms, which highlights the influence of c-FLIP proteins on this process directly at the CD95 death-inducing signaling complex. We quantitatively define how the stoichiometry of c-FLIP proteins determines sensitivity toward CD95-induced apoptosis. We show that c-FLIPL has a proapoptotic role only upon moderate expression in combination with strong receptor stimulation or in the presence of high amounts of one of the short c-FLIP isoforms, c-FLIPS or c-FLIPR. Our findings resolve the present controversial discussion on the function of c-FLIPL as a pro- or antiapoptotic protein in DR-mediated apoptosis and are important for understanding the regulation of CD95-induced apoptosis, where subtle differences in c-FLIP concentrations determine life or death of the cells.
Gesehen am 24.10.2023